2016
DOI: 10.1186/s13018-016-0389-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cephalomedullary nail fit in the femur using 3D computer modelling: a comparison between 1.0 and 1.5m bow designs

Abstract: BackgroundThe radius of curvature (ROC) misfit of cephalomedullary nails during anterograde nailing can lead to complications such as distal anterior cortical encroachment. This study quantified the anatomical fit of a new nail with 1.0-m ROC (TFN-ADVANCED™ Proximal Femoral Nailing System [TFNA]) compared with a nail with 1.5-m ROC (Gamma3 Long Nail R1.5 [Gamma3]).MethodsWe generated 63 three-dimensional models (48 female, 45 right femur) representing the cortical surfaces of the femora (31 Caucasian, 28 Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…While this study cannot confirm the ethnicity of its sample group, the cohort was from an African population not previously included in femur canal curvature studies. The results echo Schmutz's concern for anatomy-implant mismatch and should alert a surgeon to identify curvature mismatch preoperatively and use CMNs with a smaller radius of curvature or a short CMN [30]. Parameter mismatch may be due to intentional design philosophy, and for instance, the decreased CMN radius of curvature design may be a response to limit the effect of nail rotation by the surgeon to match native anteversion.…”
Section: Measurement Descriptionsupporting
confidence: 60%
“…While this study cannot confirm the ethnicity of its sample group, the cohort was from an African population not previously included in femur canal curvature studies. The results echo Schmutz's concern for anatomy-implant mismatch and should alert a surgeon to identify curvature mismatch preoperatively and use CMNs with a smaller radius of curvature or a short CMN [30]. Parameter mismatch may be due to intentional design philosophy, and for instance, the decreased CMN radius of curvature design may be a response to limit the effect of nail rotation by the surgeon to match native anteversion.…”
Section: Measurement Descriptionsupporting
confidence: 60%
“…Despite the extensive research, the results vary over a relatively large range, from 885 to 1446 mm [ 2 , 4 , 5 , 13 , 14 ]. Due to the small number of patients [ 3 , 5 ] and lack of data [ 4 , 13 ], no reliable conclusion may be drawn on differences in antecurvation between Asian and Western populations.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cortical impingement is a common phenomenon after intramedullary fixation in Asian patients with intertrochanteric fractures. 12,13,18,20,21 Chang et al 13 reviewed 158 Chinese patients and found that the incidence of anterior femoral cortical impingement was 34.8%. In this study, we found that anterior cortical impingement is popular in Chinese elderly patients with intertrochanteric fracture stabilized with an intramedullary nail.…”
Section: Discussionmentioning
confidence: 99%